The Effect of Advertising Credibility, Brand Trust, and Product Quality Perception on Consumer Repurchase Interest in Unitary Sunscreen Products - Aspi Nurani; Dadan Abdul Aziz Mubarok (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to analyze the effects of advertising credibility, brand trust, and perceived product quality on the repurchase intention of Sunscreen Unitary consumers. The study's background focuses on intensifying competition in the skincare industry and differences in consumer perceptions of promotional messages and product quality. This study employs a quantitative method, using a survey administered to 100 participants who have used Sunscreen Unitary products, with predetermined criteria. The results indicate that advertising credibility has a substantial impact on the desire to repurchase, such that the more credible the advertisement is to consumers, the greater their tendency to repurchase. Repurchase intention is positively associated with perceived product quality. making product quality a dominant thing in encouraging clients to continue using the product. Meanwhile, brand trust did now not have a significant repurchase intention, indicating that trust in the brand was not a major factor in consumers' repurchase decisions in this study. However, the simultaneous test results indicated that the three variables collectively had a significant effect on repurchase intention. The research findings show that product quality and advertising credibility play a greater position in encouraging repeat purchases than brand trust. These results can be taken into consideration by companies in formulating marketing strategies and maintaining product quality.